Study of satisfaction among domestic and foreign tourists in Tuzla - Mustafić, Ermina; Mustafić, Amir (Turisztikai és Vidékfejlesztési Tanulmányok, 2023)
Tourism is becoming an increasingly important branch of the economy for Bosnia and Herzegovina. Although strategic documents in Bosnia and Herzegovina emphasize the importance of applying a systematic approach to the development of tourism, tourism offers are not sufficiently developed yet. The problem is particularly pronounced in areas where industrial centers were developed due to the proximity of the mines, such as the city of Tuzla. Therefore, in this paper, we analyze the results of the primary survey of satisfaction in 150 tourists, which took place in the summer of 2019 while they were visiting Tuzla. The tourists were most satisfied with the local cuisine, gastronomy, and catering establishments, and the least of all, with the preservation and unpolluted environment. In this paper, through the application of the Mann-Whitney-U test, we checked whether there were statistically significant differences in satisfaction elements of the tourist offer of the city of Tuzla among domestic and foreign tourists. It was established that there is a statistically significant difference in satisfaction with accommodation between the two groups of respondents, where the respondents from other countries are significantly more satisfied than those from Bosnia and Herzegovina. In the other 16 aspects, relating to tourist offers, it was not established that there was a statistically significant difference in satisfaction between the observed two groups of respondents. Based on the analysis of the obtained research results, we provided recommendations for improving the tourist offer in order to increase the satisfaction level of tourists in Tuzla.